2018
DOI: 10.1016/j.chom.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotic-Mediated Microbiome Modulation on Rotavirus Vaccine Immunogenicity: A Human, Randomized-Control Proof-of-Concept Trial

Abstract: Rotavirus vaccines (RVV) protect against childhood gastroenteritis caused by rotavirus (RV) but have decreased effectiveness in low- and middle-income settings. This proof-of-concept, randomized-controlled, open-label trial tested if microbiome modulation can improve RVV immunogenicity. Healthy adults were randomized and administered broad-spectrum (oral vancomycin, ciprofloxacin, metronidazole), narrow-spectrum (vancomycin), or no antibiotics and then vaccinated with RVV, 21 per group per protocol. Baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 34 publications
4
104
0
Order By: Relevance
“…Furthermore, it has been indicated that early-life gut microbiota dysbiosis damages vaccine immune responses [49,50]. In this study, we found that early-life intervention with FMT-CS can reduce the risk of gut microbiota dysbiosis, as well as improve the antibody levels of M.hyo and PCV2.…”
Section: Early-life Intervention With Fmt-cs Promotes the Developmentmentioning
confidence: 60%
“…Furthermore, it has been indicated that early-life gut microbiota dysbiosis damages vaccine immune responses [49,50]. In this study, we found that early-life intervention with FMT-CS can reduce the risk of gut microbiota dysbiosis, as well as improve the antibody levels of M.hyo and PCV2.…”
Section: Early-life Intervention With Fmt-cs Promotes the Developmentmentioning
confidence: 60%
“…While there is evidence for a beneficial effect of probiotics on vaccine responses, to date, only one study has investigated the effect of antibiotics on vaccine responses in humans. This study reported that administration of antibiotics before vaccination did not alter serum immunoglobulin (Ig) A concentrations to oral rotavirus vaccine (ORV) in adults …”
Section: Introductionmentioning
confidence: 99%
“…This study reported that administration of antibiotics before vaccination did not alter serum immunoglobulin (Ig) A concentrations to oral rotavirus vaccine (ORV) in adults. 5 Determining the influence of intrinsic and extrinsic factors on vaccine antibody responses has implications for optimising vaccine recommendations and individualising vaccine schedules.…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrate that pathogen-specific MAbs do not reduce the absolute abundance, diversity, or taxonomic composition of the gut microbiome compared to those with the effects of antibiotic treatment. Such effects observed in the antibiotic treatment groups are indicative of a reduced bacterial burden in the gut and diminished capacity to prevent infection by opportunistic pathogens (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%